PENAKSIRAN DAMPAK MERGER DAN AKUISISI TERHADAP EFISIENSI PERBANKAN, ANALISIS SEBELUM DAN SETELAH MERGER DAN AKUISISI - Bryan Mikail Zaharias; Hanif Pradipta (Jurnal Ekonomi dan Pembangunan, 2025)
Corporate mergers and acquisitions are generally understood as an attempt to develop the company to better conditions, by uniting the strengths and / or compensating for the weaknesses that exist in one company with the strengths that exist in other companies. This study intends to predict when consolidation conducted by several banks in Indonesia during the period 2002 to. 2013 is able to bring the condition of these banks to a better (efficient) with Data Envelopment Analysis (DEA) approach. From the prediction result, it is known that the efficiency level of banks that have consolidated is relatively more efficient than before consolidating. From the calculation of the real efficiency of banks after the merger can prove that in general banks become more efficient after the merger and acquisition